EFEITO DA FOTOATIVAÇÃO PROLONGADA DE ADESIVOS AUTOCONDICIONANTES NA ADESÃO À DENTINA - Hass, Viviane (2012)
This study evaluated the effect of prolonged exposure times on immediate (IM) and 6-month (6M) adhesive properties: degree of conversion within hybrid layer (DC), silver nitrate uptake (SNU) and resin-dentin bond strenght (μTBS) for three one-step self-etch adhesive systems (Adper Easy Bond [EB], Clearfil S3 Bond [CS3] and Go [GO]).Ninety caries-free extracted molars were included in this study being 45 for μTBS and SNU (n=5) and 45 for DC (n=5). The dentin surfaces were bonded according to the manufacturer’s instructions, but they were light-cured for 10, 20, and 40 s at 600mW/cm2. Bonded teeth for the μTBS test were sectioned in order to obtain stick-like specimens (0.8mm2) and tested under tensile stress 0.5mm/min). Two bonded sticks from each tooth were analyzed by scanning electron microscopy for SNU. The DC within the hybrid layer were evaluated with micro-Raman spectroscopy. All tests were performed IM and at 6M. Data were analyzed by a threeway repeated measures ANOVA and Tukey´s test (alpha=0.05).The prolonged exposure times increased the DC () [10s- 67.3±19.5; 20s- 84.6 ± 12.3 e 40s- 82.9 ±13.1] for all adhesives and decreased the SNU ()[10s- 24.8 ± 13.2; 20s- 13.3 ± 7.5 e 40s- 13.5 ± 9.3] significantly for all adhesives; however significant improvements in the μTBS (MPa) [10s- 17.3 ± 3.7; 20s- 31.9 ± 4.9 e 40s- 25.0 ± 3.7] and stable bond strengths after water storage [IM- 25.2 ± 7.3; 6M- 24.2 ± 7.2] were observed only for CS3. EB [IM- 35.9 ± 4.7; 6M- 28.0 ± 6.0] and GO [IM- 25.6 ± 5.0; 6M- 14,3 ± 3,7] decreased the μTBS after 6 months. The prolonged exposure times improved the DC within the hybrid layer and reduced the SNU for all adhesives, however this did not prevent the degradation of the adhesive interface.